Kontinuitas Pesantren dan Madrasah di Indonesia - Rini Styaningsih (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Pesantren is an educational institution, a pleace for deepeningreligious knowledge of Islam, with the aim of being a cadre of moslemscholars (ulama), leaders of ummah and the leaders of the Nation. Pasantrenis unique in the learning approach and outlook on life, the level of sharedvalues, the structure of the division of authority and all aspects of educationand other community. Other Islamic educational institutions, such as, themadrassa that stood on the initiative and realization of the Islamic reform,that is, the influence of Islamic reform in the Middle East, Western educationand the traditions of Islamic education in Indonesia. The renewal includesthree things: Improvements pesantren education system, adjustments tothe Western education system, and madiation between traditionalpesantren education system and the Western education system.